A dictionary of ancient Near Eastern mythology - Leick, Gwendolyn, 1951- (Routledge, 1991)
Through accessible entries this Dictionary provides a scholarly guide to this complex and fascinating area. The wide-ranging bibliography makes use of unfamiliar sources, and there is an extensive index for ease of reference.